The influence of tissue plasminogen activator, plasminogen activator inhibitor-1, and thrombin activable fibrinolytic inhibitor on the risk of venous thrombosis: Fibrinolysis and venous thrombosis risk - Tubic, Stevan; Jozing, Marija; Ikonov, Simona; Vučković, Biljana (Medicinski časopis, 2025)
Aim: The role of the fibrinolytic mechanism in venous thrombosis risk remains controversial. The study aimed to examine the influence of tissue plasminogen activator (t-PA), plasminogen activator inhibitor-1 (PAI-1), and thrombin activatable fibrinolysis inhibitor (TAFI) on the risk of venous thrombosis.Methods: The research included 100 participants with deep vein thrombosis and 100 participants with no previous history of venous thrombosis. Global fibrinolytic activity was estimated by euglobulin clot lysis time (ECLT). The ELISA method was used for the determination of t-PA and TAFI concentrations. The chromogenic substrate method was used for the determination of PAI-1 concentrations.Results: A statistically significant difference was not obtained for t-PA and PAI-1 compared between patients and controls. Patients had a significantly higher concentration of TAFI when compared to controls. Relative risk analysis showed a three-fold increase in the venous thrombosis risk connected with suppressed fibrinolytic activity. The crude OR was 2.70 (95% CI 1.22-5.98) and adjustments for confounding yielded an OR of 3.02 (95% CI 1.26-7.22). TAFI concentrations showed influence on venous thrombosis risk, as crude OR was 2.18 (95% CI 1.19-3.99) and fully adjusted one stayed in the same range (OR 2.25; 95% CI 1.16-4.35) indicating a two-fold increase in venous thrombotic risk associated with increased TAFI concentrations. Conclusion:  Suppressed functionality of the fibrinolysis mechanism triples the risk of occurrence of deep vein thrombosis while elevated TAFI level doubles the risk of this disease. There is no influence of plasminogen concentrations, t-PA, and PAI-1 levels on venous thrombosis risk.
Keywords: fibrinolysis, deep venous thrombosis, t-PA, PAI-a, TAFI